Vibrationology: searching for resonances in the sonic architecture of matter(s) - Gray, Daniel Bruce (My University, 2021)
If we take seriously the notion that materials and space hold memory, what song would they sing? If everything is an echo of the big bang, is all connected through vibration? This speculative work thinks through the in-betweens of the materiality and implications of steel, resonances and hauntings, cities and heterotopias, sounds and silences, rhythms and frequencies. Situated in the subterranean service tunnels beneath the Wits School of Arts (WSOA) building, this creative research project comprises a series of activatable interventions which disrupt the musical instrument, the sound effects machine and the sculpture. A series of public performances took place in October 2019 and sound recordings were made over the course of the works’ development. There are two main components that form this dissertation: a lathe-cut vinyl record and this written text. It is important that these two documents are listened/read in conjunction with each other. On the record are sound recordings made of the immersive sound installation in the service tunnels beneath WSOA. In the tradition of the LP record, this written text functions as a set of extended liner notes structured into three main sections – On Resonance and Vibration, On Processes, On the Subterranean and Materiality
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts in Fine Arts to the Faculty of Humanities, School of Arts, University of the Witwatersrand, 2021